Structural Elucidation, Antioxidant Properties, and In Silico Molecular Docking of Schiff Base Complexes Derived from Naphthalene-1,8-diamine and Terephthalaldehyde - Hussein, Chanar Ahmed; Al-Nama, Khansaa Shakir; Ibrahim, Ammar Abdulsattar (Indonesian Journal of Chemistry, 2025)
By combining two mmol of naphthalene-1,8-diamine with one mmol of terephthalaldehyde, a TPAL-DAN ligand was synthesized. Six metal salts: Mn(II), Co(II), Ni(II), Cu(II), Zn(II), and Cd(II) were used to prepare six Schiff base complexes. The structure of the Schiff base (TPAL-DAN) was confirmed by FTIR, 1H- and 13C-NMR spectroscopy, mass spectrometry, and elemental analysis. Its complexes were confirmed through CHN analysis, FTIR, UV-vis spectroscopy, magnetic moment, and molar conductivity measurements. The spectral results indicate that the ligand exhibits tetradentate behavior in all six complexes, which are dinuclear metal(II) complexes, and tetrahedral geometries are observed in each metal complex. FTIR data show a lower frequency of the azomethine group in complexes than in the ligand. X-ray powder diffraction of chelates (1–4) confirms several diffraction peaks indicating the crystal system in the prepared complexes. All complexes' in vitro antioxidant capacities were estimated using DPPH free radical scavenging assays. Docking studies were conducted to predict the efficacy of the newly synthesized compounds with a breast cancer-associated protein (ID: 4jlu) and an anti-inflammatory target (ID: 1oxr). The binding energies were varied from −6.1437 to −8.1601 kcal/mol and −6.8850 to −9.9667 kcal/mol, respectively. These results highlight the potential of TPAL-DAN complexes as bioactive agents.